Adoption of climate resilient agricultural practices among the Giriama community in South East Kenya: implications for conceptual frameworks - Ziro, John Safari; Kichamu-Wachira, Edith; Ross, Helen; Palaniappan, Gomathy (Frontiers in Climate, 2023)
While quantitative studies are robust at assessing the extent of climate change adaptation, and statistical relationships among variables involved, qualitative studies are also essential to understand the social rationales underlying relationships among variables, and to identify the roles of variables that have been overlooked or are hard to measure. This study investigates factors that influence the adoption of climate resilient agricultural practices by resource-poor Giriama farmers in southeast Kenya, with a view to understanding why some smallholders from this cultural group adopt climate resilient practices, while others do not. Data was collected through in-depth interviews with 30 farmers, 15 of whom had adopted climate resilient farming practices recommended by agricultural experts, and 15 of whom had not adopted any of those practices. The adopters were market-oriented, and tended to have individual land tenure, higher levels of experience in farming, slightly larger farm sizes, middle to high school education levels, and be younger. They had access to agricultural extension, access to farm inputs, and their off-farm activities tended to be related to agricultural supply chains. Non-adopters farmed entirely for subsistence, on communal or leased land, had less formal education, and adhered strongly to cultural beliefs and practices. Their off-farm income was unrelated to agriculture. More of the adopters were males, while many of the non-adopters were female. Particular cultural practices and taboos inhibited the adoption of several of the climate resilient practices, such as planting hybrid maize, keeping dairy goats, using improved goats such as the Kenyan Alpine for breeding purposes and the use of water conservation structures for crop production. Further, the qualitative information explains how and why factors such as land ownership, gender, culture, and access to information are interrelated, in ways that are not necessarily obvious in statistical analysis. The study thus highlights issues that need to be considered in conceptual frameworks underpinning both quantitative and qualitative studies, and particularly how they interact, in order to provide the knowledge essential to policy and programs intended to enhance smallholder farmers’ adaptive capacity.